Mock Jurors’ Perceptions of Sexual Assault on a University Campus - Pica, Emily (Journal of interpersonal violence, 2021)
The purpose of this study was to examine how defendant gender, victim gender, location of sexual assault (professor’s office vs. fraternity party), and whether the defendant was intoxicated influenced mock jurors’ decisions in a sexual assault case. Mock jurors (N = 503) read a mock trial transcript depicting an alleged sexual assault and were asked to render a dichotomous verdict, continuous guilt rating, and rate their perceptions of the victim and defendant. There was no influence on mock jurors’ dichotomous verdicts. However, the presence of intoxication did influence continuous guilt ratings; intoxicated defendants elicited higher guilt ratings compared to sober defendants. Whether the defendant was intoxicated and the location of the crime were found to impact mock jurors’ perceptions of the defendant (e.g., believability, credibility); whereas the gender of the defendant affected the perceived control the defendant had over the situation. Victim gender was found to impact mock jurors perceptions of the victim, such that female victims were perceived more favorably than male victims; this may support the idea that male victims of sexual assault are generally perceived more negatively than female victims. These results, and more, are discussed in terms of the current study and the larger implications.